2016
DOI: 10.1093/bioinformatics/btw120
|View full text |Cite
|
Sign up to set email alerts
|

AlgoRun: a Docker-based packaging system for platform-agnostic implemented algorithms

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…In addition, we provide a ready-to-use Docker container for each using the AlgoRun framework (cf. [57]) and a Web interface to instances of the software running on the AlgoRun project's servers at algorun.org. This framework is used for experimental benchmarks which are presented in Section 5.…”
Section: Existing Algorithmsmentioning
confidence: 99%
“…In addition, we provide a ready-to-use Docker container for each using the AlgoRun framework (cf. [57]) and a Web interface to instances of the software running on the AlgoRun project's servers at algorun.org. This framework is used for experimental benchmarks which are presented in Section 5.…”
Section: Existing Algorithmsmentioning
confidence: 99%
“…Di Tommaso et al (2015) showed that containers have negligible impact on the performance of bioinformatics applications. Other examples of software distributed as Docker software containers include: AlgoRun (Hosny et al, 2016), which provides a modular software container with frequently used bioinformatics tools and algorithms that can be accessed through a browser or a Web application programming interface; ReproPhylo (Szitenberg et al, 2015), which implements a phylogenomics workflow with reproducibility features; and GEN3VA (Gundersen et al, 2016), which is a platform for gene-expression analysis available as a web-based system.…”
Section: /18mentioning
confidence: 99%
“…due to package dependency resolution. This problem has been addressed by the AlgoRun package (Hosny et al (2016)), providing a Docker-based repository of tools. Being a web-based service, it is limited to web-applicable data sizes, or local data must be made available to the Docker container in the cloud.…”
Section: Introductionmentioning
confidence: 99%